Management commitment and corporate sustainability integration into small and medium-scale enterprises: A mediation effect of strategic decision-making - Godfrey Adda; Ghulam Ahmed Bin Dokor; John Bosco Azigwe; Nii Afotey Odai (Economics, Management and Sustainability)
Corporate sustainability practices are vital to business survival. Hence, the need for targeted sustainable actions and corporate strategies capable of stimulating competitive advantage in terms of profitability and long-term existence of business entities. To this end, the study examines the influence of management commitment as an organisational factor on corporate sustainability integration in Ghana using corporate strategic decision-making as a mediating variable. Primary data was collected from SME owners and managers in Ghana; and the Warp partial least squares (PLS) estimation technique of the Structural Equation Model (SEM) was adopted for the analysis. The study makes a significant contribution to theory and knowledge in the context of SMEs within the corporate sustainability discourse. The study is situated on the empirical literature on the relevant concepts. This is followed by the methodology, analysis, discussions, findings, conclusions, contribution to knowledge, managerial implications, recommendations and limitations, followed by direction for future studies.